Case Report: Successful engraftment of allogeneic hematopoietic stem cells using CAR-T cell therapy as the conditioning regimen in R/R Ph+ B cell acute lymphoblastic leukemia - Han, Lu; Zhao, Ran; Yang, Jingyi; Zu, Yingling; Liu, Yanyan; Zhou, Jian; Li, Linlin; Huang, Zhenghua; Zhang, Jishuai; Gao, Quanli; Song, Yongping; Zhou, Keshu (Frontiers in Immunology, 2022)
Background Consolidative allogeneic hematopoietic stem cells (allo-HSCs) after chimeric antigen receptor T cells (CAR-T) therapy is an emerging modality in hematologic malignancies. Knowledge about the success of allogeneic hematopoietic stem cell transplantation (allo-HSCT) after CAR-T therapy without a conditioning regimen is limited. Case presentation We report a patient with relapsed/refractory (R/R) Ph+ B-cell acute lymphoblastic leukemia (ALL) who underwent anti-CD19 CAR-T immunotherapy. After 1 month of treatment, bone marrow hyperplasia remained reduced with no hematopoietic improvements. In line with this, allogeneic hematopoietic stem cells (HSCs) were extracted from an HLA-matched sibling donor and administered to the patient on day 33 after CAR-T cell therapy to support hematopoiesis. On day 40, the level of immature bone marrow lymphocytes was at 0% and minimal residual disease-negative, and the fusion gene BCR/ABL 190 was negative. Chimerism analysis showed full donor chimerism. Three months after CAR-T cells infusion, the patient was still in complete remission with full donor chimerism. However, decreased liver function with skin pigmentation and festering, indicative of acute graft versus host disease, was noted. The treatment was halted owing to financial reasons. Conclusion We report the successful engraftment of allogeneic HSCs using CAR-T cell therapy as a conditioning regimen for R/R B-ALL patients.